Analysis of the Influence of Domestic Capital Investment (PMDN) And Foreign Capital Investment (PMA) On Economic Growth In West Nusa Tenggara Province 2014 - 2023 - Anwar, Ihza Izaldi; Salmah, Emi (Formosa Journal of Science and Technology, 2024)
Regional development in Indonesia is a process that involves various aspects such as economic, social, and environmental, with the aim of improving the welfare of the community in each region. One of the key elements in regional development is investment, which plays an important role in accelerating economic growth and equality throughout Indonesia.The types of investment that enter the region can be in the form of Foreign Direct Investment (FDI) or Foreign Investment (PMA) and Gross Domestic Investment (GDI) or Domestic Investment (PMDN). The purpose of this study is to see how much influence PMDN and PMA have on economic growth in West Nusa Tenggara Province. The method used in this study is quantitative descriptive.which aims to describe or explain phenomena that occur numerically.By using Multiple Regression Analysis to analyze the relationship and interrelationship between variables in this study. Data processing in this study uses the SPSS computer program. The results of the study indicate that PMDN and PMA have a positive effect on economic growth in West Nusa Tenggara Province.